2017
DOI: 10.1177/2233865917740269
|View full text |Cite
|
Sign up to set email alerts
|

Bones of democratic contention: Maritime disputes

Abstract: While no two democratic states have fought an interstate war against each other, democratic dyads experience militarized disputes with some frequency. Previous research suggests that a large percentage of militarized disputes between two democracies involve fishing and oil resources of the sea. Yet this research selects on cases where militarized conflict occurs, and fails to consider whether democracies have more frequent diplomatic conflicts over maritime areas relative to other regime pairings. Analyzing da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Lower GDP per capita is reportedly one of the most robust predictors of social conflict, and a common hypothesis is that, as the development and macroeconomic performance of a state increases, the number of conflicts over fishery resources a country engages in decreases (Bernauer & Böhmelt, 2020; De Soysa, 2002). However, a previous study specifically on maritime conflict has shown that states with higher levels of economic development are more prone to conflict (Daniels & Mitchell, 2017). Therefore, the hypothesis here is that more developed economies have more extensive fishing operations, and are thus more likely to experience international fisheries conflict (ibid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower GDP per capita is reportedly one of the most robust predictors of social conflict, and a common hypothesis is that, as the development and macroeconomic performance of a state increases, the number of conflicts over fishery resources a country engages in decreases (Bernauer & Böhmelt, 2020; De Soysa, 2002). However, a previous study specifically on maritime conflict has shown that states with higher levels of economic development are more prone to conflict (Daniels & Mitchell, 2017). Therefore, the hypothesis here is that more developed economies have more extensive fishing operations, and are thus more likely to experience international fisheries conflict (ibid.…”
Section: Methodsmentioning
confidence: 99%
“…The commonly hypothesized relationship is that domestic institutions influence foreign policies, making democracies less likely to initiate conflict. However, because previous studies specifically on maritime conflict have shown that democracies, or powerful autocratic countries, are significantly more likely to experience conflict than dictatorships, we adopt this hypothesis as well (Daniels & Mitchell, 2017; DeSombre & Barkin, 2011; Mitchell & Prins, 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With immense, unexplored crude energy resources, this region is becoming an object of growing interest to a myriad of state and private-owned multinational energy companies, whose presence influences international relations within this region . in academic discourse, the arctic as a geographical realm presents a unique and expanding research issue (daniels & Mitchell, 2017;Marsh & Kaufman, 2012;Øverland, 2010;røseth, 2014;Wegge, 2011) . This article is aimed at inspecting the official energy strategy and foreign policy of the russian federation towards the arctic .…”
Section: Liberal Peace Promise For the Arctic: Is The Energy Policy Amentioning
confidence: 99%
“… 5. The finding by Mitchell and Prins (1999) that many jointly democratic MIDs involved maritime resources prompted the addition of maritime claims to ICOW data. While democracies do not typically challenge their neighboring democracies’ land borders, the frequency of contention over maritime spaces is most likely for jointly democratic dyads, even more so than for mixed or autocratic dyads (Daniels and Mitchell, 2016). …”
mentioning
confidence: 99%